SINTESIS SENYAWA N-(2-NITROBENZIL)-1,10 FENANTROLINIUM KLORIDA DARI 2-NITROBENZIL KLORIDA DAN 1,10-FENANTROLIN MONOHIDRAT - Noor Pratiwi, Artie; Mahfudh, Nurkhasanah (Pharmaciana, 2014)
The compound N-(2-nitrobenzyl)-1,10-phenantrolinium chloride has been synthesized bynucleophilic substitution reaction bimolecular (SN2) between the 2-nitrobenzyl chloride with1,10-fenantrolin monohydrate. This study is an experimental research of Organic Synthesis.Synthesis is done by varying the compound 2-nitrobenzyl chloride to 1.10 Phenantrolinemonohydrate ie 1:1, 3:1, 5:1 and 7:1. The purity of the compounds synthesized are determinedbased on the melting range data and TLC. Identification of the structure of the compoundssynthesized done by spectrometry UV/Visible, IR and GC-MS. The results of this research is acolorless amorphous solid from N-(2-nitrobenzyl)-1,10-phenantrolinium chloride with anoptimal yield 37%+5% and the variation of mole 2-nitrobenzyl chloride effect on the amount ofyield product, there is an optimal yield in the mole ratio of 1:1.